Extremotrophs, extremophiles and broadband pigmentation strategies in a high arctic ice shelf ecosystem - Mueller, D. (Derek); Vincent, W.F. (Warwick F.); Bonilla, S. (Sylvia); Laurion, I. (Isabelle) (FEMS Microbiology Ecology, 2005)
Remnant ice shelves along the northern coast of Ellesmere Island, Nunavut, Canada (∼83°N) provide a habitat for cryo-tolerant microbial mat communities. Bioassays of bacterial and primary production were undertaken to quantify the short-term physiological response of the mats to changes in key variables that characterize this cryo-ecosystem (salinity, irradiance and temperature). The heterotrophic versus autotrophic community responses to these stressors differed markedly. The heterotrophic bacteria were extremophilic and specifically adapted to ambient conditions on the ice shelf, whereas the autotrophic community had broader tolerance ranges and optima outside the ambient range. This latter, extremotrophic response may be partly due to a diverse suite of pigments including oligosaccharide mycosporine-like amino acids, scytonemins, carotenoids, phycobiliproteins and chlorophylls that absorb from the near UV-B to red wavelengths. These pigments provide a comprehensive broadband strategy for coping with the multiple stressors of high irradiance, variable salinity and low temperatures in this extreme cryo-environment.